Round two: repositioning the Tata Nano. Issue 4 (27th January 2016) - Sengupta, Sanjit; Ramesh, Avadhanam
Abstract : Title: – Round two: repositioning the Tata Nano. Subject area: – Marketing. Study level/applicability: – Advanced undergraduate students, MBA students, and business executives interested in enhancing their knowledge and skills of consumer behavior analysis, and marketing strategy and execution in a developing country market. Case overview: – Tata Motors Chairman, Ratan Tata, noticed that Indian families with three and four family members often commuted on a two-wheel scooter or motorbike. He had a vision to make a safe family transport for the Indian masses, a four-wheel vehicle made from scooter parts. His engineers took about five years (2003-2008) to develop the product. On January 10, 2008, Tata Motors publicly announced the Nano at the 9th Auto Expo in New Delhi at the target price of Rs 100, 0000 ($2, 500), unarguably the world ' s cheapest car. Deliveries of the Nano began in June 2009. The initial target market for the Tata Nano was comprised of individuals and families who relied on a two-wheeler for transport. The value proposition was a safe, affordable, and attractive car. Initial reactions from industry analysts, dealers, and consumers were overwhelmingly positive.In February 2010, Carl-Peter Forster (born in the UK and raised in Germany) was appointed Group CEO of Tata Motors. Monthly sales kept increasing until a high of 9, 000 units in July 2010, then there were consistent declines for the next four months to just 509 units in November. In December 2010, ten months after being on the job, Carl-Peter Foster had to turn around the sales performance of Tata Nano. Expected learning outcomes: – Get students to appreciate the importance of understanding consumer behavior in the design and execution of marketing strategy. Get students to understand the concept of value and how it is important at any price level, especially in comparing and contrasting consumer behavior across developed and developing country markets. Get students to understand how marketing strategy is designed (target market selection and positioning) and executed after understanding consumer behavior. Get students to understand how the marketing programs (marketing-mix) reinforce product positioning. Supplementary materials: – Teaching notes.